Solubility Enhancement of Simvastatin by Co-compression with Hydrophilic Polymers (PEG & PVP) and surfactant (SLS) - Bindu Madhavi, B.; Kusum, B.; Ramalingam, R.; Arjun, G.; Shekar, K.; Udaya Sri, E.; Vijetha, N.; Ravinder Nath, A.; Banji, David (Asian Journal of Chemistry, 2011)
The aim of the present investigation is to enhance the dissolution of simvastatin (SIM) by cocompression with hydrophilic polymers [poly(ethylene glycol) and poly(vinyl pyrolidone)] and surfactant (sodium lauryl sulfate). Phase solubility studies are conducted by using poly(ethylene glycol) (PEG), poly(vinyl pyrolidone) (PVP) and sodium lauryl sulfate (SLS). The apparent stability constant (Ka), thermodynamic parameters like Gibb's free energy change (ΔG), Enthalpy change (ΔH) and Entropy change (ΔS) are calculated from the phase solubility data. All the values indicated that the used carriers were favouring the dissolution of drug in water and this is increased with increase in the carrier concentration. After confirming the positive effect on the dissolution of drug, the carriers were co-compressed with drug and other ingredients in to tablets. FTIR studies revealed no interaction between drug and ingredients. The prepared tablets were evaluated for tablet properties like hardness, weight variation, thickness, content uniformity, friability and disintegration time according to USP. It was found that the tablets passed all the above tests as the values were within the prescribed limits according to USP. From the dissolution studies, it was known that there is tremendous enhancement in the dissolution rate of pure drug with the co-compression of carriers. The cumulative % drug releases of pure simvastatin was 14.3 % and of the tablets containing carriers were 89.9 (sodium lauryl sulfate), 74.6 [poly(ethylene glycol)] and 81.1 [poly(vinyl pyrolidone)] after 3 h.